Plasma Aluminum Concentrations in Pediatric Patients Receiving Long-Term Parenteral Nutrition. (July 2015) - Courtney-Martin, Glenda; Kosar, Christina; Campbell, Alison; Avitzur, Yaron; Wales, Paul W.; Steinberg, Karen; Harrison, Debra; Chambers, Kathryn
Background : Patients receiving long-term parenteral nutrition (PN) are at increased risk of aluminium (Al) toxicity because of bypass of the gastrointestinal tract during PN infusion. Complications of Al toxicity include metabolic bone disease (MBD), Al-associated encephalopathy in adults, and impaired neurological development in preterm infants. Unlike the United States, there are no regulations regarding Al content of large- and small-volume parenterals in Canada. We, therefore, aimed to present our data on plasma Al concentration and Al intake from our cohort of pediatric patients receiving long-term PN. Methods : Plasma Al concentration was retrospectively gathered from the patient charts of all 27 patients with intestinal failure (IF) receiving long-term PN at The Hospital for Sick Children, Toronto, Canada, and compared with age- and sex-matched controls recruited for comparison. In addition, Al concentration was measured in PN samples collected from 10 randomly selected patients with IF and used to determine their Al intake. Results : The plasma Al concentration of patients with IF receiving long-term PN was significantly higher than that of control participants (1195 ± 710 vs 142 ± 63 nmol/L; P < .0001). In the subgroup of 10 patients for whom Al intake from their PN solution was determined, mean ± SD Al intake from PN was 15.4 ± 15 µg/kg, 3 times the Food and Drug Administration upper recommended intake level, and Al intake was significantly related to plasma Al concentration ( P = .02, r 2 = 0.52). Conclusion : Pediatric patients receiving long-term PN for IF in Canada are at risk for Al toxicity.